Problemas en la configuración legal del artículo 247 del COIP, dentro de los delitos ambientales cometidos en el régimen especial de Galápagos - Zavala Robalino, Katherine Elizabeth (2018)
Through the legal norms, the ownership of rights is established, since 2008, the constitutional provision establishes rights to Nature, which is why its legal status rises to be Subject of Rights. In Ecuador, the Constitution contains principles and rights in favor of nature, and penalties are also established for environmental crimes in the Comprehensive Organic Criminal Code…….